Commitment to Applying Green Accounting in Industrial Companies in the Kingdom of Saudi Arabia to Achieve the Dimensions of Sustainable Development - AwadAlla Abobaker; Ardi Gunardi (Universitas Pasundan, 2023)
This study aims to examine the degree of commitment of industrial enterprises in the Kingdom of Saudi Arabia to green accounting, contributing to sustainable development goals. Utilizing descriptive-analytic and deductive methods, a unique questionnaire was circulated to a random sample of thirty industrial enterprises. The collected data were processed using the SPSS statistical application. The results indicate a significant lack of industrial firms’ dedication to the application of green accounting. It also identifies existing barriers impeding the implementation of green accounting to achieve sustainable development objectives. The study proposes an increased awareness of the concept of “green accounting” and calls for the introduction of laws and accounting standards necessitating businesses to adopt green accounting practices. The significance of the study lies in its distinct focus on the adoption of green accounting in Saudi Arabian industrial enterprises, highlighting both the challenges faced and potential solutions.